Incident investigation in Pakistan's fertilizer industry—Common safety management system failures and issues. Issue 4 (27th January 2014) - Rashid, Muhammad Imran; Ramzan, Naveed; Almas, Qandeel
<x xml:space="preserve">Abstract</x> The learning from operational incidents plays a key role in improving the performance and safety of the chemical process plants. In this article, the incidents occurred during January 2011 to April 2012 in different sections, that is, Ammonia, Urea, and Utility Units of fertilizer sector in Pakistan have been analyzed using Why Tree analysis. The aim is to identify the failures in the safety management system to prevent the incidents. One thousand and fifteen, root and contributing causes identified in investigations strongly assert that improvement in safety management systems could have prevented or mitigated the intensity of many of the occurred incidents/accidents. The flaws in mechanical integrity, maintenance procedures and operating procedures, and job risk assessment are the most common recurrent as root cause failures of safety management system. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 399–404, 2014